2002
DOI: 10.1016/s1044-0305(02)00416-6
|View full text |Cite
|
Sign up to set email alerts
|

On the specificity of cyclodextrin complexes detected by electrospray mass spectrometry

Abstract: ␣-cyclodextrin complexes with linear ␣, -dicarboxylic acids were investigated by electrospray mass spectrometry. These hydrophobic complexes are known to have an equilibrium binding constant that increases with the diacid chain length. However, the electrospray mass spectrometry (ES-MS) spectra showed that the relative intensity of the complex did not vary significantly with chain length. This contradiction is caused by a contribution of nonspecific adducts to the signal of the complex in ES-MS. In order to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 46 publications
(57 reference statements)
3
121
0
5
Order By: Relevance
“…Energy-resolved mass spectrometry (ERMS) has been used to investigate the structures of ions and noncovalently associated ions [31][32][33][34][35][36][37][38][39][40]. We have analyzed isomeric oligosaccharides based on ERMS and shown that (1) the primary glycosidic linkage is more stable than the secondary glycoside linkage; and (2) ␣-glyco-␣ sides are more labile than ␤-glycosides, through inves-␤ tigation of malto (␣1¡4)-, ¡ ¡ isomalto (␣1¡6)-, and cello (␤1¡4)-oligosaccharid ¡ ¡ e [26] and trisaccharide libraries with the ␣/␤-Fuc-(1 ␤ ¡6)-␣/␤-Gal-(1 ␤ ¡6)-␣/␤-Glc-octyl ␤ sequence [27].…”
Section: Erms Analysismentioning
confidence: 99%
“…Energy-resolved mass spectrometry (ERMS) has been used to investigate the structures of ions and noncovalently associated ions [31][32][33][34][35][36][37][38][39][40]. We have analyzed isomeric oligosaccharides based on ERMS and shown that (1) the primary glycosidic linkage is more stable than the secondary glycoside linkage; and (2) ␣-glyco-␣ sides are more labile than ␤-glycosides, through inves-␤ tigation of malto (␣1¡4)-, ¡ ¡ isomalto (␣1¡6)-, and cello (␤1¡4)-oligosaccharid ¡ ¡ e [26] and trisaccharide libraries with the ␣/␤-Fuc-(1 ␤ ¡6)-␣/␤-Gal-(1 ␤ ¡6)-␣/␤-Glc-octyl ␤ sequence [27].…”
Section: Erms Analysismentioning
confidence: 99%
“…In the present experiments the formation of nonspecific adducts can't be precluded, but in any case their effect on the performed experiments did not affect the calculations, as shown from the excellent linearity of eq 8 and the agreement with the value obtained spectroscopically. However, in cases where nonspecific aggregation occurs in a high degree, the study of these complexes by using the total intensity may appear to be tricky and therefore it is proposed to apply the method presented by Gabelica and coworkers [43] to estimate the contribution of nonspecific adducts. The formation of 2:2 guest:CD complexes can not be precluded, although the features of the selected guests minimize this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies report on more or less successful analyses of noncovalent complexes where hydrophobic forces are considered to play a dominant role for the stability [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Liu et al [19,20] showed the preservation of hydrophobically stabilized complex between bovine β-lactoglobulin and its natural ligands, fatty acids, for the fraction of ESI-generated ions.…”
Section: Introductionmentioning
confidence: 99%
“…CDs allow for the formation of inclusion complexes with various nonpolar molecules in polar solvents [34]. Several studies have reported on the detection of inclusion complexes between CDs and aromatic or aliphatic guests, amino acids, peptides, and drugs by ESI-MS [23][24][25][26][27][28][29][30][31][32][33]. However, in these studies, guest molecules bore at least one polar group that pointed out of the cavity and enabled hydrogen bonding or dipole-dipole interactions with hydroxyls of the CD rim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation